Peran Teknologi Pendidikan dalam Menumbuhkan Kemampuan Berpikir Kritis Peserta Didik di SD Negeri 1 Wargabinangun Kecamatan Kaliwedi - Khasanah, Mar'atul; Rohmah, Eliyah; Putra, Nugraha Permana (Universitas Syiah Kuala, 2025)
This research aims to determine the role of educational technology in fostering the critical thinking abilities of fifth-grade students at SD Negeri 1 Wargabinangun, Kaliwedi Subdistrict. The background of the study is the lack of integration of critical thinking habits in learning and the scarcity of varied learning resources. The method used is qualitative, with data collection techniques including interviews, observations, and documentation. The results show that the use of educational technology can enhance learning activities as well as students' critical thinking skills. Out of 33 students, 28 (80%) have completed the requirements, while 5 (20%) others have not yet completed, surpassing the target set at 75%. Thus, educational technology has proven to be effective in improving students' critical thinkingabilities.